Hot deformation behavior of nano-Al2O3-dispersion-strengthened Cu20W composite - An Junchao (Science and Engineering of Composite Materials, 2021)
Nano-Al2O3 dispersion-strengthened Cu20W composite was fabricated by vacuum hot-pressing sintering process. The electrical conductivity, relative density, and Brinell hardness were tested, respectively. The gleeble-1500D thermomechanical simulator was used to conduct isothermal compression with strain rates ranging from 0.001 to 10 s−1 and the temperatures ranging from 650 to 950°C. The microstructure of the Cu–Al2O3/20W composite was observed using an optical microscope and a transmission electron microscope, and the true stress–strain curves were analyzed. In addition, the influence of the nano-Al2O3 and tungsten on the thermal deformation process of the composite was analyzed. The relationship and interaction among work hardening, dynamic recovery, and dynamic recrystallization were illustrated. The results show that nano-Al2O3 particles pin dislocations and inhibit dynamic recovery and dynamic recrystallization. Consequently, the Cu–Al2O3/20W composite has typical dynamic recovery characteristics. Hence, the Cu–Al2O3/20W composite possesses outstanding high-temperature performance. The optimal processing domain of the Cu–Al2O3/20W composite ranged from 760 to 950°C with strain rates ranging from 0.01 to 0.1 s−1. Furthermore, the constitutive equation of the Cu–Al2O3/20W composite is established, and the activation energy is 155.069 kJ mol−1.